Representasi Nilai-Nilai Budaya dalam LPP Lokal (Studi terhadap Program Siaran TVRI Sumatera Barat yang Bermuatan Kearifan Lokal) - Wakidul Kohar; Usman Usman (Universitas Islam Negeri Imam Bonjol Padang, 2015)
This research based on the assumption that the media helps to establish the reality of real life in the community. The reality rises because of media workers process language. Associated with it, TVRI of West Sumatra, which has existed in this region, was not fully provide enough space in the broadcast activities to represent Minangkabau culture. It happened because of three things, which is associated with the processes, strategies and discourse to be fought in the broadcast television. The method used in this study is a content analysis with a qualitative approach, in reading the manuscript broadcast program, watching the programs and interviewing the producers and the audience with accidental sampling. Theory of agenda setting theory is used to understand and read the data. This study even found in the process and strategy, the programs do not begin with research of needs and viewers, because it was said the programs were patterned on the package of programs from several years ago. Whereas the values behind the broadcast programs of TVRI West Sumatera are the value of deliberation, togetherness and express egalitarian society